Odpowiedzi

2010-02-04T18:05:32+01:00
A) -(2x-1)=4
-2x+1=4
-2x=3
-x=3/2
x=-1 1/2

b)2(x+1)=x
2x+2=x
x=-2

c)2x-(3x+1)=6
2x-3x-1=6
-x=7
x=-7

d)-4+x=2(3-x)
-4+x=6-2x
2x+x=6+4
3x=10
x=10/3
x=3 1/3

Nie wiem, czy dobrze rozczytałem podpunkt d
2010-02-04T18:09:58+01:00
A) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 /:(-2)
x=-1,5

b) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2

c)2x-(3x+1)=6
-2x-3x+1=6
-5x=5 /:(-5)
x=-1

d)-4=x)=2(3-x) ->jeśli = to +
-(4+x)=6-2x
-4-x=6-2x
-x+2x=6+4
x=10

Mam nadzieję, że pomogłam i że jest dobrze:)